Eneolithic, Yamnaya, Catacomb and Babyno Culture Cemeteries, Pidlisivka, Barrow 1, Yampil Region, Vinnitsa Oblast: Archaeometry, Chronometry and Taxonomy - Klochko, Viktor I.; Kośko, Aleksander; Razumov, Serhiy M.; Włodarczak, Piotr; Żurkiewicz, Danuta (Baltic-Pontic Studies, 2017)
The paper presents excavation results and analytical studies concerning the taxonomic classification of a funerary site identified with the communities of the early ‘barrow cultures’ settling the north-western Black Sea Coast in the 4th/3rd-2nd millennium BC. The study focuses on the ceremonial centres of the Eneolithic, Yamnaya, Catacomb and Babyno cultures.